2017
DOI: 10.1017/jfm.2017.204
|View full text |Cite
|
Sign up to set email alerts
|

Laminar hypersonic leading edge separation – a numerical study

Abstract: This paper describes laminar hypersonic leading edge separation. Such a configuration of separated flow was originally studied by Chapman et al. (NACA Tech. Rep. 1356, 1958) at supersonic Mach numbers as it is particularly amenable to theoretical analysis and assumes no pre-existing boundary layer. It can be considered as a limiting case of much studied generic configurations such as separation at a compression corner and separated flow behind a base. A numerical investigation is described using a compressible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
26
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 54 publications
7
26
0
Order By: Relevance
“…It is interesting to point out the similarity between the results of figure 11 and earlier results of wall temperature effects on leading edge separation (Khraibut et al. 2017; Khraibut 2018), which also showed that the second shear stress minimum becomes shallower but increases in magnitude with increasing wall temperature. It is possible that both effects (bluntness and wall temperature) result in an overall reduction of local Reynolds number relieving gradients near the second minimum.…”
Section: Resultssupporting
confidence: 80%
See 4 more Smart Citations
“…It is interesting to point out the similarity between the results of figure 11 and earlier results of wall temperature effects on leading edge separation (Khraibut et al. 2017; Khraibut 2018), which also showed that the second shear stress minimum becomes shallower but increases in magnitude with increasing wall temperature. It is possible that both effects (bluntness and wall temperature) result in an overall reduction of local Reynolds number relieving gradients near the second minimum.…”
Section: Resultssupporting
confidence: 80%
“…It is worth noting that this particular feature also resembles the effect of wall temperature on the heat flux knee in a leading edge separation configuration shown in Khraibut et al. (2017).…”
Section: Resultssupporting
confidence: 71%
See 3 more Smart Citations